Pembelajaran Keagamaan dengan Kitab Klasik dalam Pelestarian Budaya Pesantren di Pondok Pesantren Uswatun Hasanah - Muhammad Tolib; Erawadi Erawadi; Sumper Mulia Harahap (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
This study examines the phenomenon of digitalization that affects students' lives, with schools striving to maintain morals through religious education using traditional Islamic texts (kitab kuning) to preserve the pesantren culture. The focus of this research includes: 1) The stages of teaching kitab kuning in the preservation of pesantren culture at Pondok Pesantren Uswatun Hasanah, 2) The strategies for teaching kitab kuning for this purpose, and 3) The implications of this teaching on the preservation of pesantren culture. This research is qualitative with a multisite approach, using in-depth interviews, participant observation, and documentation techniques. The results show that teaching kitab kuning begins with lalaran nadhom, followed by the presentation of material by the teacher according to the lesson plan (RPP), and ends with quizzes and homework. The teaching strategy involves selecting books according to class levels, the qualifications of teachers, and the methods of sorogan, bandongan, and wetonan. The aim of the education is to instill good morals in students, with competency tests and remedial measures for those who have not met the target. The implications of this teaching include the success of the institution in shaping students with good morals and proper worship, thereby ensuring the preservation of pesantren culture in the millennial era.